Motor Conduction Studies and Handgrip in Hereditary TTR Amyloidosis: Simple Tools to Evaluate the Upper Limbs - Di Stefano, Vincenzo; Thomas, Ewan; Giustino, Valerio; Iacono, Salvatore; Torrente, Angelo; Pillitteri, Guglielmo; Gagliardo, Andrea; Lupica, Antonino; Palma, Antonio; Battaglia, Giuseppe; Brighina, Filippo (Frontiers in Neurology, 2022)
Purpose: Hereditary transthyretin amyloidosis with polyneuropathy (ATTRv) is caused by mutations in the TTR gene, leading to misfolded monomers which aggregate generating amyloid fibrils. The clinical phenotype is heterogeneous, characterized by a multisystemic disease affecting the sensorimotor, autonomic functions along with other organs. Materials and methods. All patients were assessed with a complete neurological assessment, neurophysiological evaluation of the median nerve and handgrip analysis. The data are presented as means and standard deviations. Parametric and non-parametric assessments have been used to identify differences between groups. Pearson’s correlation has been carried out when appropriate. Results. Twenty patients with ATTRv (66.1±8.4 years; 8 females) and 30 controls (61.1±11.6 years; 16 females) were enrolled. Handgrip strength was reduced in ATTR patients in both right and left hands compared to controls. Significant differences were found between patients and controls in the right (handgrip right, HGSR TTR 21.1 ± 13.0 kg vs HGSR Control 29.4 ± 11.3 kg, p=0.017) and left (handgrip left, HGSLTTR 22.2 ± 10.7 kg vs HGSL Control 31.0 ± 11.3 kg, p=0.007). NIS and CMAP amplitude of the median nerve were related to HGS measures for both hands in ATTRv patients. Conclusions. The progression of bilateral carpal tunnel syndrome is related to neurophysiological data in the median nerve in ATTRv. Also, handgrip measures might represent an important tool for the assessment of disease progression in ATTRv. We propose a combined use of CMAP amplitude and HGS for the assessment of hand motor strength in ATTRv.